Prevention of competition by competition law: Evidence from unbundling regulation on fiber-optic networks in Japan - Naoaki Minamihashi (Osaka University, Institute of Social and Economic Research (ISER), 2011)
This paper finds that a regulation that promotes competition in one market may decrease competition in other related markets. Policy makers in the telecommunication industry currently are facing an important decision about whether to continue unbundling regulations on new optical-fiber lines. I find that unbundling regulation prevents new providers from building optical-fiber networks, by estimating a dynamic entry game with a dataset of fiber-optic network constructions in Japan from 2005 to 2009. In particular, when a new technology is introduced, unbundling regulation has an oligopolization effect on the regulated firms. This finding in the Japanese telecommunications industry suggests that unbundling regulation during periods of new technology diffusion may reduce the price of service but also decrease competition in the infrastructure market.
Additional information: The 13th ISER-Moriguchi Prize (2010) Awarded Paper.
Keywords: K21; L43; L96; 330; Unbundling; FTTH; Entry and Exit; Dynamic Game; Fiber-optic Networks; Entflechtung; Telekommunikationsnetz; Breitbandkommunikation; Netzregulierung; Markteintritt; Marktaustritt; Dynamisches Spiel; Japan